Transcriptional network involving ERG and AR orchestrates Distal-less homeobox-1 mediated prostate cancer progression - Sakshi Goel (Nature Portfolio, 2021)
Distal-less homeobox 1 (DLX1) is reported as a prostate cancer (PCa) diagnostic biomarker, but the mechanism for its upregulation in PCa is unclear. Here the authors show that ERG, AR and FOXA1 transcriptionally regulates DLX1 expression in PCa, and the inhibition of this ERG/AR transcriptional circuitry with a BET inhibitor reduces the oncogenic effects of DLX1.